OQÍWShÍLARǴA NOQATTÍŃ KOORDINATALARÍ TÚSINIGIN VEKTORDAN PAYDALANÍP ÚYRETIW USÍLÍ - Tanirbergenov, S.A.; Abdieva, G.K. (SCIENCE and SOCIETY, 2025)
The article deals with vectors and rectangular coordinate system. Here is a way to explain the concept of the coordinate of a point given in the mathematics of the school course using vectors.